Oestrogen receptors in oesophageal cancer - De Rosa, Antonella (2018)
Introduction: Oesophageal cancer is more common in men than women. Oestrogen, which mediates its effects via oestrogen receptors (ERs), may be responsible for the gender disparity. This thesis investigates the role of ERs in oesophageal cancer development and explores potential therapeutic possibilities.